Eurasian contribution to the last glacial dust cycle: how are loess sequences built? - D.-D. Rousseau; A. Svensson; M. Bigler; A. Sima; J. P. Steffensen; N. Boers (Climate of the Past, 2017)
The last 130 000 years have been marked by pronounced millennial-scale climate variability, which strongly impacted the terrestrial environments of the Northern Hemisphere, especially at middle latitudes. Identifying the trigger of these variations, which are most likely associated with strong couplings between the ocean and the atmosphere, still remains a key question. Here, we show that the analysis of δ 18 O and dust in the Greenland ice cores, and a critical study of their source variations, reconciles these records with those observed on the Eurasian continent. We demonstrate the link between European and Chinese loess sequences, dust records in Greenland, and variations in the North Atlantic sea ice extent. The sources of the emitted and transported dust material are variable and relate to different environments corresponding to present desert areas, but also hidden regions related to lower sea level stands, dry rivers, or zones close to the frontal moraines of the main Northern Hemisphere ice sheets. We anticipate our study to be at the origin of more sophisticated and elaborated investigations of millennial and sub-millennial continental climate variability in the Northern Hemisphere.